The Relationship Between Family Support and Quality of Life in Patients with Type II Diabetes Mellitus - Maidayani, Maidayani; Amelia, Rosi; Syukriadi, Syukriadi; Fazlylawati, Ellyza; Mansuriza, Mansuriza; Rizki, Muhammad (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2025)
Patients with type II diabetes mellitus tend to receive less support from their families, which affects their quality of life. Family support is important in the management of diabetes mellitus prevention to minimize the occurrence of complications. This research examines the connection between family support and quality of life among type II diabetes mellitus patients at Krueng Barona Jaya Community Health Center. The study employed a descriptive correlational design using a cross-sectional methodology. Data was gathered between May 20 and June 18, 2025. From a population of 118 type II diabetes patients, 53 participants were chosen through purposive sampling. The researchers used the Hensarling Diabetes Family Support Scale and Diabetes Quality of Life questionnaires for data collection. Statistical analysis included univariate and bivariate analysis (chi-square test) conducted with SPSS software. The results of the study indicate that informational support (p=0.000), emotional support (p=0.003), appreciative support (p=0.003), and instrumental support (p=0.003) influence the quality of life of patients with Type II Diabetes Mellitus. In conclusion, there is a relationship between informational, emotional, appreciative, and instrumental support and quality of life among patients with type II diabetes mellitus. Family involvement in treatment is very important, especially in terms of emotional and instrumental support. The quality of life of patients with type II diabetes mellitus improves when accompanied by optimal family support. Patients who are always accompanied by their families are seen to regularly seek treatment by visiting health facilities and adhering to their diet.